Sistem Penghitung Protein Telur Berdasarkan Volume Menggunakan Komputasi Citra Metode Cakram Berbasis Raspberry Pi Dan Perangkat Android - Muhammad Riyyan Royhan; Hurriyatul Fitriyah; Agi Putra Kharisma (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Inappropriate daily intake of protein can cause various diseases. Information about protein content of a food is very useful because with that information, people can know and regulate the level of proteins that they consume. Therefore, chicken eggs as a cheap and easy source of animal protein are important foods to know about their protein value. Research on eggs that have been widely made makes information about egg protein content can be known from the weight of the egg itself. Egg weight can also be found based on its volume. Egg volume can be calculated from the surface area of the egg using disk method. The surface area, and volume of egg can be known by computing the image of the egg. The Image computation to find egg volume can be done by using Raspberry Pi which is assisted with an Android device as an image taker, and also as a system interface. This research embodies a system that is capable of processing egg images to calculate the value of volume, weight, and protein content of the eggs. The system is tested for its accuracy based on its measurement results of the volume and the weight of the eggs, compared to the measurement results of ordinary measuring instruments. The final results of the test show that the system has an accuracy value of 95.76% for measurement of egg weight and 93.94% for measurement of egg volume.